The impact of brand experience on the memory formation. Issue 1 (19th November 2019) - Legendre, Tiffany S.; Cartier, Elizabeth A.; Warnick, Rodney B.
Abstract : Purpose: The purpose of this paper is to examine the effectiveness of brand experiences on visitors' memory formation and their revisit intention to a special event. Design/methodology/approach: This study collected survey data from the Great New England Air Show to examine the soundness of the proposed theoretical model. Data were analyzed with partial least squares–structural equation modeling. Findings: The results indicate an individual's brand experience in the context of a special event can assist him/her in becoming more involved and finding meaningfulness in the experience, and form greater readiness to store memory of the event. Memory formation triggered by brand experience can help event practitioners anticipate positive behaviors of visitors after the experience. Practical implications: The results suggest that event marketing managers and decision makers should create strong brand experiences focused on a mix of sensory, affective, intellectual and behavioral messages linked to the larger brand knowledge and memory formation. Originality/value: The development of a theoretical model explaining brand experience with the purpose of explaining the internalization of brand experience in memory formation was documented and the study validated the brand experience concept in a non-monetary setting.